D-CREEA: DSML para criação de jogos analógicos educacionais de cartas - Silva, Rubens Anderson de Sousa (2022)
Educational games can promote a playful learning experience by solving problems related to the educational content of a subject, placing the student as the main actor in the learning process. In addition, with analog educational games, this experience provides a face-to-face discussion on the subject, with tactile interaction and quick feedback. However, developing an educational game is not trivial, since it requires knowledge in education, game design and scientific background. To facilitate this process, one can use the concept of MDE (Model-Driven Engineering) and DSML (Domain-Specific Modeling Language), in a standard and semi-automated way. In this context, the objective of this work is first to develop a DSML to create educational analog card games, called D-CreEA Card Games, and then a WEB platform based on the DSML. The motivation of this work is to help professors in the Computing field to construct playful learning methodologies using games. To evaluate D-CreEA, Computer Science professors had used the platform to develop a card game through the manipulation of a standard game, at all stages of the game development. The evaluation revealed that the D-CreEA platform can indeed be useful for creating educational analog games, satisfying all aspects of quality considered, according to the participants.